PERLINDUNGAN HUKUM WARGA NEGARA ASING DALAM PEMBUATAN AKTA JUAL BELI BANGUNAN YANG DIBUAT OLEH NOTARIS, STUDI KASUS : PUTUSAN MA NOMOR 673/K/PDT/2010 - NANA NANA (PREMISE LAW JURNAL, 2016)
Buy and sell on a building, along with its land, in Batam, by using a Notarial deed is commonly done by foreign citizens since residence, usually constructed by developers, is based on management rights. Governmental Regulation No. 41/1996 requires foreign citizens who have residence to register their building rights as the right of use. Lack of their legal knowledge of the right and obligation in owning residence in Indonesia becomes one of the factors which cause them to lose their right of use on their residence; in this case, they have not registered the right of use in one year since the transact was done. This case can be seen in the Ruling of the Supreme Court No. 673K/pdt/2010. Every individual has the right to get legal protection and so do foreign citizens who own residence in Indonesia.  Legal protection should be in accordance with the responsibility. In general, foreign citizens consider that sale contract signed by a Notary can become evidence of full ownership of building. Actually, it has to be followed up by making sale contract before PPAT (official empowered to draw up land deeds) as the legal basis for registering the right of use. A Notarial deed is authentic evidence which is used as an analysis when there is a problem with sale contract owned by foreign citizens and with supporting document which will be used by them as evidence when they have transferred the building and its land to the other parties. Keywords: Legal Protection, Foreign Citizen, the Right of Use